Spatial heterogeneity in density dependence across life‐history stages drives the dynamics of a bird metapopulation - Tor Hansson Frank; Peter Sjolte Ranke; Hamish Burnett; Paul Acker; Thor Harald Ringsby; Jonathan Wright; Henrik Jensen; Bernt‐Erik Sæther; Yimen G. Araya‐Ajoy (Ecology, 2026)
Density‐dependent effects on individual vital rates play a critical role in determining a population's equilibrium size and rate of return following stochastic disturbances. In fragmented landscapes, spatial variation in density dependence across life‐history stages causes heterogeneity in limitations of population growth, which influences extinction‐persistence dynamics. As habitat loss leads to increased landscape fragmentation, understanding the factors driving variation in the strength of density dependence across life‐history stages is necessary to assess population viability and guide conservation strategies. We quantified spatial variation in the strength of density dependence across life‐history stages in a house sparrow metapopulation encompassing 11 islands in northern Norway, collected from 1994 to 2022. Our findings reveal that increased density negatively affects the demographic contributions of individuals to population growth. We found a pronounced negative effect of density, especially on survival, which was stronger in juveniles than in adults. In contrast, there was no clear impact on nestling production. We recorded stronger density dependence on islands further from the mainland, likely due to harsher environmental conditions during winter. Furthermore, the density dependence of survival was stronger in juveniles relative to adults on islands where adult survival contributed more to population growth than on islands where juvenile survival was more important. This indicates that the strength of density dependence at different life‐history stages was related to each island's average pace‐of‐life. Thus, this study demonstrates potential links between spatial variation in density dependence across life‐history stages, population dynamics, and life‐history evolution.